A SURVEY ON SECURITY IN MOBILE ADHOC NETWOR (International Journal of Engineering and Computer Science, 2017)
Today, the popular technology in Networking talks about MANET(Mobile Adhoc Network). It makes tremendous change in wireless network.   A mobile adhoc network is an wireless network connected with  autonomous mobile nodes which are self configured  and dynamic.   Security is a main concern for protecting the communication between mobile nodes. The security design of the mobile adhoc network leads many problems such as shared wireless medium,, severe resource constraints, and highly dynamic network environment. In this paper we identify the security issued relevant to this problem, analyze the challenges to security design, and evaluate the state-of-art security proposals etc. The security solution is given according to the survey.